PSO based Direct Power Control for a Multifunctional Grid Connected Photovoltaic System - Bengourina Mohamed Rida; M. Rahli; S. Slami; L. Hassaine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents a grid-connected photovoltaic system (PV) used as a shunt active power filter (SAPF) to provide the power factor correction, harmonic elimination, reactive power compensation and to simultaneously supply power from a PV system to the utility. A direct power control (DPC) method is used for controlling the system to feed the photovoltaic energy in synchronization with grid and provide power quality improvement. The PI parameters of DC-link voltage controller are tuned using the Particle Swarm Optimization (PSO) algorithm without the need for an exact mathematical model of system. This PI-PSO controller gives better results for robustness, harmonic minimization and reduces the overshoot and undershoots of PI controller. The overall control of system is tested in Matlab/Simulink environment. Then, the simulations results demonstrate the robustness and feasibility of proposed method.